Nutrition Status, Fall Risk, and Use of Community Food Programs in Community-Dwelling Older Adults. (7th June 2021) - Tarleton, Emily; Gell, Nancy; Eckert, Caitlin
Abstract: Objectives: Falls are a leading cause of injury, death, functional impairment, and a driver of health costs and utilization in older adults. However, falls among older adults are mostly preventable and therefore fall risk reduction is a high value target for intervention. Poor nutritional status is a risk factor for falls and impedes recovery from falls. Understanding the role of rurality and seasonality in the relationship between falls, nutrition, and access to and use of community nutrition programs is imperative to planning future interventions to decrease fall risk. This pilot study will evaluate these relationships over time in a cohort of older Vermonters within the context of rurality and seasonality. Methods: Using an observational, analytic study design, we will collect data at two points: baseline (fall 2020) and 6 months later (spring 2021) via an online survey. Adults, 60 and older and residing in Vermont year round were eligible to participate. We collected demographic and community program utilization data as well as responses to three validated questionnaires: CDC STEADI fall risk checklist, Seniors in the Community: Risk Evaluation for Eating and Nutrition, Version III, and the 2-item Food Insecurity screen. We used descriptive statistics to analyze demographic data and chi square analyses to identify associations between food insecurity, nutrition risk, fall risk and falls. Results: At baseline, 53% of the 708 respondents had an elevated fall risk, 42% had a fall in the past six months, 11% were experiencing food insecurity, and 55% were at a nutrition risk. Additionally, 72% of respondents self-identified as living in a rural setting. Overall, community resource utilization was low: 2% of respondents reported using Meals on Wheels, 7% SNAP, and 8% food banks. We found a significant association ( P  < 0.001) between fall risk and food insecurity, fall risk and nutrition risk, and food insecurity and nutrition risk. Conclusions: Our baseline data provides evidence for a significant relationship between nutrition, food insecurity, and fall risk in community-dwelling older adults. Follow-up data will provide important information for understanding these relationships over time and within the context of rurality and seasons, particularly as this data was collected during the COVID-19 pandemic. Funding Sources: Vermont Biomedical Research Network